2012
DOI: 10.1212/wnl.0b013e3182661f3c
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-related hemangioblastoma progression and complications in von Hippel-Lindau disease

Abstract: Pregnancy in patients with VHL disease induces cerebellar hemangioblastoma progression and causes a high VHL disease-related pregnancy complication rate. We recommend intensified surveillance of patients with VHL disease, especially of cerebellar hemangioblastomas during preconception care and pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 9 publications
0
40
0
4
Order By: Relevance
“…Ye et al 2 prospectively followed a group of 36 women of childbearing age with VHL with serial craniospinal MRI over a mean period of 7.5 years, showing no difference in the rate of tumour progression or oedema formation between the nine patients who became pregnant and those who did not. An uncontrolled retrospective analysis by Frantzen et al 3 demonstrated significant progression of cerebellar haemangioblastomas, but no progression in tumours in the spine, retina, kidney or adrenal glands in 29 women with 48 pregnancies. Of the women in this study, 17% suffered complications in pregnancy related to VHL, of which 50% were life threatening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ye et al 2 prospectively followed a group of 36 women of childbearing age with VHL with serial craniospinal MRI over a mean period of 7.5 years, showing no difference in the rate of tumour progression or oedema formation between the nine patients who became pregnant and those who did not. An uncontrolled retrospective analysis by Frantzen et al 3 demonstrated significant progression of cerebellar haemangioblastomas, but no progression in tumours in the spine, retina, kidney or adrenal glands in 29 women with 48 pregnancies. Of the women in this study, 17% suffered complications in pregnancy related to VHL, of which 50% were life threatening.…”
Section: Discussionmentioning
confidence: 99%
“…A hyperdynamic circulation with reduced plasma osmolality and serum albumin in pregnancy has been postulated to increase oedema surrounding intracranial tumours, which may explain our patient's deterioration in the second trimester. 3,6 A humoral link causing tumour progression has been widely postulated but not clearly established.…”
Section: Discussionmentioning
confidence: 99%
“…Current data consists primarily of case series, even the largest of which may lack power due to small sample sizes. [2][3][4] Use of large administrative databases can facilitate studies of pregnancy in rare disorders, as shown by our prior work with neurofibromatosis 1, another neurogenetic tumor suppressor syndrome. Using a population-based database, we found that pregnant women with NF1 experienced increased maternal morbidity, including higher rates of hypertensive and cerebrovascular complications, than the general population.…”
Section: Pregnancy Complications In Women Withmentioning
confidence: 99%
“…In this regard, the radiosensitizing effects of tamoxifen or its inhibitory effects on protein kinase c activity may be more important than its anti-estrogenic properties [20]. The presence of gonadal steroid receptors or biological responsiveness to reproductive hormones has also been described in cases of pituitary adenomas, acoustic neuromas, oligodendrogliomas, anaplastic ependymomas, lymphomas, hemangioblastomas, primitive neuroectodermal tumors and breast cancer metastases to the neuraxis [20,118,119,120]. …”
Section: Gonadal Hormones and Nervous System Neoplasmsmentioning
confidence: 99%